Understanding relationship between precipitation/flood and human mobility using smartphone data from Senegal - Tan, Leonard Teck Siong (2015)
In order to better improve living conditions in country like Senegal, large dataset of mobile phone dataset are made available for researchers and interested parties to work on them with the goal to help the targeted population. For this project, mobile phone dataset of Senegal and the precipitation dataset were processed and worked on in hope to develop some findings that will be beneficial to the targeted population, in this case the Senegalese. Senegal has been a victim to the natural disaster of flooding and heavy rainfall, and the aim of this project is to understand the relationship between the precipitation dataset and human mobility from the mobile phone dataset in Senegal. The results of this project failed to reject the null hypothesis as there were not enough evidence available to suggest the null hypothesis is false; the results were not consistent and therefore unable to conclude whether there are any correlation between the precipitation dataset and the human mobility from the mobile phone dataset.